Management of quality-related costs: the case of Portuguese companies - Pires, A. R.; Cociorva, A.; Saraiva, M.; Novas, J. C.; Rosa, A. (Total Quality Management and Business Excellence, 2013)
The traditional view of quality-related costs (QRC) tries to justify investment in prevention as a way to reduce the costs of failure. But this static view must counter a more dynamic vision that fosters continuous improvement and assesses the costs and benefits of implementing techniques and methods of quality management, such as certification of ISO 9001systems. However, it is unknown whether such companies are also engaged in the management of QRC arising from activities undertaken, either at the level of monitoring, or coming from failures, and if such organisations verify (or not) the recovery of investments in quality. In this sense, the present article aims to provide insight into the procedures adopted by Portuguese companies in managing QRC, and to assess the extent to which management reports allow the analysis of quality costs and contribute to the related planning and control activities. The results of this study showed that there is hardly any assent to the implementation of formal mechanisms for planning and control of QRC, and to the explicit identification and segregation of those costs in management reports.